Hubungan Genetik antara Domba Wonosobo (Dombos), Domba Ekor Tipis (DET) dan Domba Batur (Dombat) Melalui Analisis Polimorfisme Protein Darah - F Noviani; Sutopo Sutopo; E Kurnianto (Universitas Sebelas Maret (UNS), 2013)
The objective of this study was to evaluate the genetic relationships among Wonosobo sheep (Dombos), Thin-Tailed sheep (DET) and Batur sheep (Dombat) through blood protein polymorphism analysis by using electrophoresis Polyacrylamid Gel Electrophoresis-Thin Layer Electrophoresis (PAGE-TLE). The blood of the 20 head of Dombos (Wonosobo regency), 20 head of DET (Semarang regency) and 20 head of Dombat (Banjarnegara regency) were used as materials. Six locus of blood plasma protein were observed, then the gene frequency, individual heterosigosity, averageheterosigosity and genetic distance among three breed were calculated. The results showed that the locus of pre-albumin (Pa), albumin (Alb), ceruloplasmin (Cp), transferrin (Tf), post-transferrin (P-tf) and amylase-I (Am-I), at DET, Dombos and Dombat were polymorphic (0,380-0,454). In conclusion, the DET and Dombat indicated the closer genetic relationship compared to DET-Dombos and Dombos-Dombat.Key words: sheep, polymorphism, genetic relationship